PENERAPAN SISTEM ANTRIAN PADA FASILITAS PELAYANAN PADA LOKET PENGAMBILAN OBAT - Diana Khairani Sofyan; Amri Amri; Abdul Aziz (Universitas Teuku Umar, 2019)
Puskesmas has a counter service, because every patient at the puskesmas who will take the medicine is served through the counter. In general, each puskesmas has a minimum number of one counter according to service needs. The problem that occurs in the Puskesmas is that it always causes queues for patients. Queues that occur in the Kuala District Public Health Center are at the drug collection counter. The volume of arrivals is in the queue per day of 109, with a study time of 5 days. While at the drug collection counter, it only has one counter. The aim of the study was to find out whether the number of drug collection counters in the Puskesmas was optimal and to find out how many counters should be owned by the Puskesmas so that they could serve patients optimally. The method used in this study is a queuing model to determine the performance of drug collection counters. In addition simulation techniques are also used to provide an overview of a system to evaluate and improve system performance. From the results of calculations and simulations of the Arena, it was found that the number of optimal counters for drug collection counters was 4 counters. From the results of the calculation of simulation output, it can be seen that the simulation model scenario 2 is better than the simulation model scenario 1 and scenario 3, because in scenario 2 there are 4 counters with a waiting time of 0.8546 minutes, thus reducing the number of patient queues.